Learning Arabic through the Tamyiz Online Method in a Psycholinguistic Perspective of the General Society - Moh. Fahmi Majid; Achmad Tito Rusady (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2022)
This study aimed to describe how the tamyiz method became one of the ideal possibilities for the general people as a means of learning Arabic, and interpreting the Qur'an and the yellow book more thoroughly. In this study, researchers employed a descriptive qualitative methodology based on several literature studies and grounded theory. Researchers are also directly involved in the intended chase. This research focuses on 3 things, namely: the tamyiz method via online, psycholinguistics, and digital learning. The results show that there are many basic psycholinguistic theories contained in the formation and application of this method. The reason why this tamyiz method is a choice in learning Arabic translation, is the hope that the participants of this method can understand more deeply the Qur'an in the era of digital learning that has been growing rapidly in recent years. Based on the findings, it can be concluded that the Tamyiz approach is a dynamic and student-centered method of active learning. With a uniform theoretical basis from the psycholinguistic side in various aspects of the learning system, this method can be the answer to various questions about how the general public can continue to learn and understand Arabic in this digital era.